Parameters evaluation of the co-composting of sewage sludge and grass clippings using the respirometric method - Scoton, Edvaldo José [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP]; Bezerra, Barbara Stolte [UNESP]; Renófio, Adilson [UNESP]; Akutsu, Jorge (Inderscience Publishers, 2015)
Despite several previous studies, a better understanding of the sewage sludge composting process is necessary. This study evaluates the use of an automated respirometer with hermetic rotary reactor (ARHRR) to evaluate O2 consumption and CO2 production during the co-composting of sewage sludge and grass clippings. For this research, we used an apparatus consisting of an automated respirometer with hermetic rotary reactor (ARHRR), a gas analyser, and a microcomputer for automatic data acquisition. The results show that the use of the ARHRR reduces the composting time to 30 days and produce no odour during the process. The compost thus produced showed a carbon/nitrogen ratio of 16:1 and a pH of 8.02, making it suitable for use as an agricultural fertiliser. The evaluation of the ARHRR by means of co-composting sewage sludge and grass clippings enables its use as a parameter for the design, operation and control of the composting process applied to a real scale process.
Keywords: Composting; Grass residue; Respirometric method; Sewage sludge; Solid waste